Analysis of the validity and reliability of the Photo Finish® smartphone app to measure sprint time - Marco-Contreras, L. A.; Bataller-Cervero, A. V.; Gutiérrez, H.; Sánchez-Sabaté, J.; Berzosa, C. (Sensors, 2024)
In athletic training and research, the evaluation of sprint speed is widely used, and its accurate measurement is especially demanding. High-cost photocells are the gold-standard system for sprint time assessment, although low-cost smartphone applications can be a suitable option. This study assesses the validity and reliability of an application to measure sprint time compared to photocells. Five physically active subjects completed six sprints of 10 m and 20 m at maximal speed and a 5 m go and return sprint to evaluate the validity of the Photo Finish® app (Version 2.30). To assess reliability, six trials of 5 m go and return sprints were measured by two smartphones. The validity results showed a mean bias of 0.012 s (95% CL: 0.000, 0.024) between the application and the photocells for the 10 m sprint, 0.007 s (95% CL: -0.007, 0.022) for the 20 m sprint and 0.005 s (95% CL: -0.005, 0.017) for the 5 m go and return test. The results also found R2 between both systems (R2= 0.9863, 0.990 and 0.958) for each distance (10 m, 20 m and 5 m go and return, respectively). As for reliability, the application showed outstanding consistency between two smartphones operating simultaneously (ICC 0.999; R2: 0.999). This study shows that the Photo Finish® app is an accurate and reliable tool to measure sprint time with an error of 0.09 s.